Factors involved in intensive care unit mortality following medical retrieval: Identifying differences between intensive care unit survivors and non‐survivors. (22nd May 2013) - Visser, Philip; Harriss, Linton R; Hart, Graeme K; Bohensky, Megan; Sundaresan, Lalitha; Kennedy, Marcus
Abstract Objective The study aimed to determine factors related to ICU mortality in critically ill patients transferred by Adult Retrieval Victoria (ARV) medical staff. Patients who died in ICU after interhospital transfer were compared against those who survived. Methods This was a retrospective cohort study of ARV cases between 1 January 2009 and 30 June 2010. Retrieval data were linked with data from the ANZICS CORE APD (Australia and New Zealand Intensive Care Society Centre for Outcome and Resource Evaluation Adult Patient Database). Victoria Data Linkage (VDL) performed linkage of data. Data included demographic and clinical data obtained during transfer and clinical data recorded in ICU. Results Of the 601 cases transferred by ARV during the study period, 549 cases were eligible for linkage to 25 543 ANZICS APD case records for the same period. VDL matched 460 of these cases (83.8%). Mortality rate in the matched sample was 13.9%. Variables associated with mortality were: advanced age (odds ratios [OR] 1.02, 95% confidence interval [CI] 1.00–1.04, P = 0.02), principal referral problem cardiac (OR 1.84, 95%CI 1.02–3.32, P = 0.04), lower mean arterial blood pressure (OR 0.97, 95% CI 0.95–0.99, P = 0.005) and tachycardia (OR 1.02, 95% CI 1.00–1.03, P = 0.008) on arrival at destination hospital. Conclusions Advanced age, lower mean arterial blood pressure and tachycardia towards the completion of transfer were associated with increased ICU mortality in this population. Clinicians should be aware of the additional risk for cardiac patients.